Pengaruh Pengetahuan Investasi dan Return Saham Terhadap Minat Mahasiswa Dalam Berinvestasi di Galeri Investasi Syariah - Anisa Pitriyani; Romi Adetio Setiawan; Citra Liza (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The capital market is a meeting place for investors and issuers where one of the parties included as an investor is a student at the Faculty of Islamic Economics and Business who is expected to become an expert investor in the field of sharia capital markets. Students' investment interest is influenced by several factors, including investment literacy and stock returns. One of the capital market instruments is investment, namely capital investment carried out by a person or legal entity with the aim of increasing the value of capital. Based on the factors found, researchers are interested in researching students' interest in investing. Researchers want to know the results of the influence of the two factors, namely investment knowledge and stock returns on students' interest in investing so that it can become a benchmark for institutions, especially the Sharia Investment Gallery, in attracting investor interest, especially students of the Sharia Economics Study Program, Faculty of Islamic Economics and Business. The factors that will be used by researchers are the quality of investment knowledge and stock returns. Thus the title of this research is